Adaptation to an Intracellular Lifestyle by a Nitrogen-Fixing, Heterocyst-Forming Cyanobacterial Endosymbiont of a Diatom - Flores, Enrique; Romanovicz, Dwight K.; Nieves-Morión, Mercedes; Foster, Rachel A.; Villareal, Tracy A. (Frontiers in Microbiology, 2022)
The symbiosis between the diatom Hemiaulus hauckii and the heterocyst-forming cyanobacterium Richelia intracellularis makes an important contribution to new production in the world’s oceans, but its study is limited by short-term survival in the laboratory. In this symbiosis, R. intracellularis fixes atmospheric dinitrogen in the heterocyst and provides H. hauckii with fixed nitrogen. Here, we conducted an electron microscopy study of H. hauckii and found that the filaments of the R. intracellularis symbiont, typically composed of one terminal heterocyst and three or four vegetative cells, are located in the diatom’s cytoplasm not enclosed by a host membrane. A second prokaryotic cell was also detected in the cytoplasm of H. hauckii, but observations were infrequent. The heterocysts of R. intracellularis differ from those of free-living heterocyst-forming cyanobacteria in that the specific components of the heterocyst envelope seem to be located in the periplasmic space instead of outside the outer membrane. This specialized arrangement of the heterocyst envelope and a possible association of the cyanobacterium with oxygen-respiring mitochondria may be important for protection of the nitrogen-fixing enzyme, nitrogenase, from photosynthetically produced oxygen. The cell envelope of the vegetative cells of R. intracellularis contained numerous membrane vesicles that resemble the outer-inner membrane vesicles of Gram-negative bacteria. These vesicles can export cytoplasmic material from the bacterial cell and, therefore, may represent a vehicle for transfer of fixed nitrogen from R. intracellularis to the diatom’s cytoplasm. The specific morphological features of R. intracellularis described here, together with its known streamlined genome, likely represent specific adaptations of this cyanobacterium to an intracellular lifestyle.